Avaliação da conectividade de remanescentes de vegetação nativa em matriz agrícola, considerando os índices ecológicos para aves - Matos, Tatiana Possati Vieira de (2015)
The replacement of natural cover, by other land-uses, associate with the forest fragmentation process can result in the decrease of forest connectivity in the landscapes. The diagnosis of landscape structure, through the landscape ecology metrics, intende to direct the restoration activities and the evaluation of forest connectivity. The study aimed at the evaluation of forest connectivity in the the National Forest (FLONA) Capão Bonito and its surrounding area, in the state of São Paulo, Brazil. We produced a land-use/land-cover map, through supervised digital classification, and calculated the landscape metrics (patch and class level) for study area. Selected metrics (Area, ENN and Shape) were used in the production of sustainability index (SI). The forest patches were classified in levels of priority for forest restauration, through SI. In order to identify the forest connectivity was calculated the Integral Index Connectivity (IIC) and we realized the redundancy analysis (RDA), the non-metric multidimensional scaling (NMDS) and multiple regression. Detection was performed by the bird fixed points method and the composition of bird community was obtained through the abundance of species. The diversity index of Shannon Weaver (H ') and species richness was calculated. The land-use/land-cover map indicated that the landscape´s matrix is agriculture, with native forests occupying only 24.45%. The main focuses of forest restoration are the fragments associated with the highest values of SI, because they can guarantee the maintenance and/or the restoration of biodiversity. It was obtained that the IIC =1.000 m influenced in the variance of the birds community and, the shape metric was the main factor that influenced in the composition, richness and diversity of birds. We concluded that is possible to evaluate the connectivity axes using avufauna. The RDA permits the identification of maximum spread for birds. The shape of forest fragments is one of the main factors, influencing in bird community because it is relate with edge effect and forest landscape connectivity. The SI is a simple and effective method for express the priority patches for forest restoration.